Career Trajectories in Online Freelance Platform Work - Blaising, Allie; Kulkarni, Chinmay; Dabbish, Laura (2020)
ABSTRACT Over the last decade, the emergence of online freelance platforms has re-configured work in fundamental ways. Yet, despite the rapid growth of this work, we have a limited understanding of its long term evolution, experience, or sustainability or how it influences broader career goals. To address this gap, we conducted a set of surveys and longitudinal interviews with online freelancers. We find that online freelancing supports career transition, new career domain exploration, and entrepreneurial skill development. To realize these opportunities, online freelancers must develop strategies to combat a set of burdens that represent the overhead of maintaining an online freelancing career. As a growing number of organizations, clients and workers turn to online freelance platforms in the wake of the COVID-19 crisis, the challenges we identified have important implications for design and policy efforts to support a new future of online freelancing. ABOUT THE AUTHOR/S Allie Blaising HCI Institute ablaisin@andrew.cmu.edu Allie Blaising is a researcher in the Connected Experience Lab within the Human-Computer Interaction Institute (HCII) at Carnegie Mellon University. She received her bachelor's degree from California Polytechnic University, San Luis Obispo. Previously, she was a research intern at Stanford University in the Computer Science department with Michael Bernstein and Mark Whiting and research intern through the HCII REU program with Chinmay Kulkarni. Chinmay Kulkarni HCI Institute chinmayk@cs.cmu.edu Chinmay Kulkarni is an Assistant Professor of Human Computer Interaction at Carnegie Mellon University, where he directs the Expertise@Scale lab. In his research, Chinmay introduces new collaborative computer systems that help people learn and work better; typically, these systems use the large scale ofparticipation to yield benefits that are otherwise not achievable. Laura Dabbish HCI Institute & Heinz College dabbish@cs.cmu.edu Laura Dabbish is an Associate Professor in the Human-Computer Interaction Institute (HCII) at CMU with appointments in the Heinz College of Public Policy and Information Systems Management and Societal Computing. She directs the Connected Experience Lab and studies online collaboration and digitally enabled platform-based work. She is a World Economic Forum Young Global Scientist, and has received research funding from the NSF, Sloan Foundation, IBM Research, Snap Research and Google. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).